2007
DOI: 10.1128/aem.01536-06
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of Ammonia-Oxidizing Bacteria under Long-Term Application of Mineral Fertilizer and Organic Manure in a Sandy Loam Soil

Abstract: The effects of mineral fertilizer (NPK) and organic manure on the community structure of soil ammoniaoxidizing bacteria (AOB) was investigated in a long-term (16-year) fertilizer experiment. The experiment included seven treatments: organic manure, half organic manure N plus half fertilizer N, fertilizer NPK, fertilizer NP, fertilizer NK, fertilizer PK, and the control (without fertilization). N fertilization greatly increased soil nitrification potential, and mineral N fertilizer had a greater impact than org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
130
5
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(166 citation statements)
references
References 43 publications
(65 reference statements)
24
130
5
7
Order By: Relevance
“…6), confirming similar results obtained from various agricultural soils (Phillips et al 2000;Chu et al 2007;Ouyang et al 2016). It has been suggested that Nitrosospira cluster 3 often outcompeted other Nitrosospira under fertile soil conditions (Tourna et al 2010).…”
Section: Aoa-otu7 (256bp)supporting
confidence: 84%
“…6), confirming similar results obtained from various agricultural soils (Phillips et al 2000;Chu et al 2007;Ouyang et al 2016). It has been suggested that Nitrosospira cluster 3 often outcompeted other Nitrosospira under fertile soil conditions (Tourna et al 2010).…”
Section: Aoa-otu7 (256bp)supporting
confidence: 84%
“…Alternatively, perhaps in this ratio the plants were able to take up most of the nutrients before the AOB community could respond. In contrast, Chu et al (2007) observed similar DGGE bands and amoA copy numbers in NPK, NP and NK treatments in agricultural soils. Experiments that apply different ratios of N and P would be necessary to tease apart the interactive effects of these nutrients.…”
Section: Effects Of Nitrogen and Phosphorusmentioning
confidence: 66%
“…In a different New England salt marsh, Horner-Devine et al, (2004) observed a correlation between AOB composition and phosphate concentrations; pairwise samples with more similar phosphate concentrations contained more similar communities. In agricultural soils, Chu et al (2007) found differences in DGGE banding patterns of the amoA gene between control and PK (phosphorus and potassium)-enriched plots, but did not find differences in amoA copy numbers (Chu et al, 2008) or soil nitrification potentials.…”
Section: Effects Of Nitrogen and Phosphorusmentioning
confidence: 99%
“…However, while Nitrosopira cluster 2 was relatively abundant in three forest soil libraries (BF1, BZ2, BZ3) with reasonably low pHs (4.05-5.36), there was no overall correlation between the relative abundances of cluster 2 in the libraries and soil pH (ρ=0.15, P=0.3) suggesting that cluster 2 AOB do not necessarily have higher relative abundances in acidic soils. Likewise, results from previous studies [14][15][16]20] have contributed to the hypothesis that representatives of Nitrosospira cluster 3 are likely to be relatively more abundant in soils with higher levels of N availability. If we examine the proportional abundances of Nitrosospira cluster 3, we see no correlations with our measured indices of N availability (N mineralization rates and extractable NH 4 + or the sum of NH 4 + plus NO 3 − concentrations, P>0.4 in all cases).…”
Section: Composition Of the Soil Aob Communitiesmentioning
confidence: 82%
“…We do know that distinct soils often harbor distinct AOB communities. A number of environmental factors, including vegetation type [9][10][11], soil nutrient levels [12][13][14][15][16], soil microclimate [13,17,18], and management practices [19][20][21], have been found to have an important influence on the spatial variability exhibited by AOB communities. However, because most studies have compared AOB communities across a rather limited number of samples, with one notable exception being the study by Avrahami and Conrad [18], it has been difficult to ascertain which soil biotic and abiotic characteristics are related to AOB community composition across larger spatial scales.…”
Section: Introductionmentioning
confidence: 99%